1979
DOI: 10.2134/agronj1979.00021962007100050037x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nitrapyrin from Soils as Affected by pH and Temperature1

Abstract: Little information is available on soil characteristics that influence the persistence of nitrapyrin [2‐chloro‐6‐(trichloromethyl) pyridine] in soil. Knowledge concerning these characteristics could be helpful in determining the most effective time of nitrapyrin application and in identifying soils in which the most effective inhibition of nitrification by nitrapyrin might be expected. The objective of this study was to evaluate the effects of soil pH and temperature on the disappearance of nitrapyrin and ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…The concentrations of NO 3 − -N in the soils of urea + nitrapyrin treatment across the pH gradient at day 28 were lower than those in the soils of urea treatment at corresponding pH levels, and the net nitrification rates in the soils of urea + nitrapyrin treatment across the pH gradient were also lower than those in the soils of urea treatment (Table 1), indicating that nitrapyrin inhibited nitrification and its inhibitory effect varied with soil pH. This is consistent with the finding reported previously (Hall 1984; Chancy and Kamprath 1982; Degenhardt et al 2016; Sims and MacKown 1987; Touchton et al 1979; Hendrickson and Keeney 1979). For example, (Hendrickson and Keeney 1979) found that the inhibitory efficiency of nitrapyrin increased with soil pH.…”
Section: Discussionsupporting
confidence: 90%
“…The concentrations of NO 3 − -N in the soils of urea + nitrapyrin treatment across the pH gradient at day 28 were lower than those in the soils of urea treatment at corresponding pH levels, and the net nitrification rates in the soils of urea + nitrapyrin treatment across the pH gradient were also lower than those in the soils of urea treatment (Table 1), indicating that nitrapyrin inhibited nitrification and its inhibitory effect varied with soil pH. This is consistent with the finding reported previously (Hall 1984; Chancy and Kamprath 1982; Degenhardt et al 2016; Sims and MacKown 1987; Touchton et al 1979; Hendrickson and Keeney 1979). For example, (Hendrickson and Keeney 1979) found that the inhibitory efficiency of nitrapyrin increased with soil pH.…”
Section: Discussionsupporting
confidence: 90%
“…Plot between natural logarithm of nitrapyrin persistence versus time on days at different concentrations (2 µg•g -1 and 4 µg•g -1 ) of soil sample B too high. These results are in accordance with the earlier reports in which it has been reported that the half-life of nitrapyrin is reduced with increasing temperatures (Touchton et al 1979). Higher persistence of NP at higher application rate (4 µg•g -1 ) can also be attributed to delayed nitrification in case of higher fortification rate.…”
Section: Resultssupporting
confidence: 93%
“…Inhibitors such as AM are chemically unstable at soil pH ≤ 4, and thus are not suitable for acidic soils (Toyoda et al, 1978). Nitrapyrin is stable in the pH range of 2.7 to 11.9 (Keeney, 1980;Slangen and Kerkhoff, 1984), but less effective at soil pH > 6.5 and at high levels of SOM (Hendrickson et al, 1978;Touchton et al, 1979). The rate of nitrapyrin required for effective inhibition of nitrification in soils increases with soil pH and SOM (Goring, 1962a;Keeney, 1986).…”
Section: Soil Chemical and Physical Propertiesmentioning
confidence: 99%
“…Most NIs including nitrapyrin, DCD, AM, and DMPP are very effective at ≤5 • C. Under low temperatures, the inhibitory effect can last up to six months, making inhibitors suitable for applications in fall and winter (Slangen and Kerkhoff, 1984;. However, as the temperatures increase above 10 • C, there is a linear decrease in the effectiveness of most of the nitrification inhibitors; at temperatures of ≥25 • C, the inhibitory effect lasts only two to three weeks at the most (Touchton et al, 1979;Zerulla et al, 2001). The inverse relationship between soil temperature and inhibitor effectiveness is largely due to less persistence of many inhibitors in the soil, and increased biological activity of nitrifiers at higher temperatures (Gomes and Loynachan, 1984).…”
Section: Abiotic Factorsmentioning
confidence: 99%